Supplementation of Crataegi fructus alleviates functional dyspepsia and restores gut microbiota in mice - Hao, Liyu; Yu, Zeyue; Sun, Jianhui; Li, Zongyuan; Li, Jianliang; Deng, Yurong; Huang, Hanhui; Huo, Hairu; Li, Hongmei; Huang, Luqi (Frontiers in Nutrition, 2024)
Functional dyspepsia (FD), also known as non-ulcerative dyspepsia (UND), is a common digestive system disease in clinics. In this study, an FDthe model of FD was established using by means of hunger and satiety disorders combined with an intraperitoneal injection of L-arginine (L-Arg). Indices used to evaluate the efficacy of hawthorn in FD mice include The small intestinal propulsion rate, gastric residual rate, general condition, food intake, amount of drinking water, gastric histopathological examination, and serum nitric oxide (NO) and gastrin (GAS) levelscontents were used as indices to evaluate the efficacy of hawthorn ion FD mice. Based on the intestinal flora and their metabolites, short-chain fatty acids (SCFAs), the mechanism of action of 样式定义: 正文: 行距: 2 倍行距 带格式的: 缩进: 左侧: 0 厘米, 首行缩进: 0 字符 Crataegi Ffructus (hawthorn) on FD was studied. The fecal microbiota transplantation (FMT) test was used to verify whether hawthorn alteredplayed the above role by adjusting the structure of the intestinal flora. The results showed that hawthorn improved FD byhad a good effect on improving FD, which could significantly reducinged the gastric residual rate, increasinged the intestinal propulsion rate, increasinged food intake and drinking water intake, and increasinged the levels of gastrointestinal hormones. SimultaneouslyAt the same time, hawthorn could elevated the expression of Substance P(SP) and 5-Hhydroxytryptamine expression (5-HT) in the duodenum, reduced serum and degrade the content of Nitric Oxide(NO) levelsin the serum, and increased the expression of vVasoactive iIntestinal pPeptide (VIP) expression in the duodenum. Notably, , hawthorn could also increased the abundance of beneficial bacteria and SCFAs-producing bacteria in the intestines of FD mice, decreased the abundance of conditional pathogenic bacteria, and significantly increased the SCFA content of SCFAs in feces at the same time. It was suggested that tThe mechanism by whichof hawthorn improvesing FD may be related to the regulation of intestinal flora structure and the production of SCFAs.